The Effect of Contextual Teaching Learning on Solving Story Problems Ability Students of MTsN 1 Medan - Yuldina Husna Ritonga; Zainal Azis (JMEA : Journal of Mathematics Education and Application, 2022)
This research aims to find out the effect of using contextual teaching learning on solving story problems ability at first year MTsN 1 Medan students 2020/2021 on integer countsubject matter. The population of this study was all students of class VII MTsN 1 Medan totaling 351 people divided into 11 study groups. This sampling technique using cluster random sampling so class VII-1 uses a contextual learning model and VII-2 uses a conventional learning model. This research type is quasi experiment with the research instrument tested the ability to solve story problems wich consisted of five essay question. The results of the study with the help of SPSS version 25.0 show that there is an influence of the contextual teaching learning on the ability to solve story problems. This based on a significant value 0,031 0,05.